Unmetabolized serum folic acid and its relation to folic acid intake from diet and supplements in a nationally representative sample of adults aged ≥60 y in the United States(1)(2)(3)(4) - Bailey, Regan L (American Society for Nutrition, 2010)
Background: Unmetabolized serum folic acid (UMFA) has been detected in adults. Previous research indicates that high folic acid intakes may be associated with risk of cancer. Objective: The objective was to examine UMFA concentrations in relation to dietary and supplemental folate and status biomarkers in the US population aged ≥60 y. Design: Surplus sera were analyzed with the use of data from the National Health and Nutrition Examination Survey (NHANES) 2001–2002, a cross-sectional, nationally representative survey (n = 1121). Results: UMFA was detected in 38% of the population, with a mean concentration of 4.4 ± 0.6 nmol/L (median: 1.2± 0.2 nmol/L). The group with UMFA (UMFA+) had a significantly higher proportion of folic acid supplement users than did the group without UMFA (60% compared with 41%). UMFA+ men and women also had higher supplemental and total (food + supplements) folic acid intakes than did their counterparts without UMFA. Forty percent of the UMFA+ group was in the highest quartile of total folic acid intake, but total folic acid intake was only moderately related to UMFA concentrations (r(2) = 0.07). Serum folate concentrations were significantly higher in the UMFA+ group and were predictive of UMFA concentrations (r(2) = 0.15). Serum 5-methyltetrahydrofolate and vitamin B-12 concentrations were higher in the UMFA+ group, whereas there was no difference between the 2 UMFA groups in red blood cell folate, serum homocysteine, or methylmalonic acid concentrations. Conclusions: Approximately 40% of older adults in the United States have UMFA that persists after a fast, and the presence of UMFA is not easily explained in NHANES by folic acid intakes alone. Given the possibility that excessive folic acid exposure may relate to cancer risk, monitoring of UMFA may be warranted.